The Simulation of Wind Behavior in Sedimentation on the Slope in the Laboratory - Amjad Maleki; AbbasAli Vali; Vajiheh Kahrarian (جغرافیا و پایداری محیط)
The wind erosion, digging the land, the transfer of materials, and cramming it in a different spot change the earth face. This study aims at examining the behavior of wind in sedimentation on the surfaces with different slopes in laboratory. To fulfill this an experiment was done in the laboratory in the form of a random pattern with 7 Tamaris including the slope of zero percentage, ±%2 ±%5, ±%10. The results of radiance analysis show a meaningful difference in the slopes less than %1 in sedimentation by tamaris. Comparing the average of tamaris by Duncan shows that the most sedimentation occurs in the surface without any slope so that with the growth of slope (direct and inverted) the sedimentation decreases. In order to express the relations between the percentage of sloping and sedimentation, the regression analysis has been used; it shows the decrease of sedimentation of wind as the slope of the surface grows. To examine the sedimentation of different slopes the model 2 was chosen, the others being the model 3 and the linear model. Finally, using the regression analysis, the relation between distance of tunnel exit and extent of sedimentation has been examined, which showed that the wind behavior and it’s function of sedimentation is different depending on the rate of slopes. Finally the process of sedimentation was specified for each surface by appropriate models: Including the linear model, model2, and model3 for the positive slope (direct) and the zero slope and model 2 for the negative slope (inverted). According to the results of this study, the laboratory simulation could be used as an appropriate method for studying the wind behavior in sedimentation on surfaces with various features.